Factors contributing to heavy metal accumulation in sediments and in the intertidal mussel Perna perna in the Gulf of Annaba (Algeria) - Belabed, Bourhane-Eddine; Laffray, Xavier; Dhib, Amel; Fertouna-Belakhal, Mouna; Turki, Souad; Aleya, Lotfi (Marine pollution bulletin, 2013)
•Heavy metals in sediments and in the intertidal mussel Perna perna in the Gulf of Annaba.•Anthropogenic pollution is obvious in P. perna tissues and in the sediment.•Levels were nevertheless within the limits of public health standards.•P. perna seems to be a useful bioindicator of man’s influence on the distribution of heavy metals. This paper presents the results of a seasonal survey of heavy metals accumulated in sediments and in the soft parts of the body of the mussel Perna perna at four stations in the Gulf of Annaba (Algeria). Pooled soft tissues from 10 mussels representing the entire range of sizes were digested in nitric acid. Statistical analysis reveals a significant seasonal effect on all the measured metals, the highest values being recorded in winter. With the exception of Cr, the levels for all metals were significantly higher in the east, at the outlet of the Seybouse River, than at all other monitoring stations. The study also shows that north-western waters are subject to a significantly lower degree of heavy metal pollution than elsewhere in the gulf. Levels were nevertheless within the limits of public health standards. The results confirm the usefulness of P. perna as a bioindicator for heavy metal pollution.